Effect of Allium sativum, Citrus limon and Carica papaya extract on intestinal parasitosis - Palacios Zevallos, Juana Irma (2021)
Objective. To evaluate the effect of Allium sativum (garlic), Citrus limon (lemon) and Carica papaya (papaya) extracts in the treatment of intestinal parasitosis. Methods. Experimental, prospective, cross-sectional study. The sample size was calculated by non-probabilistic purposive sampling. To evaluate the effect of the extract, the experimental antiparasitic extract based on Allium sativum (garlic), Citrus limon (lemon) and Carica papaya (papaya) was first developed; it was administered every 12 hours for five days; and the sample (feces) was collected for parasitological analysis. The samples for data analysis were subjected to the McNemar nonparametric test and Fisher’s exact test. Results. The statistical analysis showed a significant difference (p < 0.05) between before and after administering the experimental antiparasitic extract, both in protozoa (Giardia lamblia) and helminths (Taenia solium). In relation to the three age groups (6 to 7 years, 8 to 9 years and 10 to 12 years), there was no statistically significant difference in the antiparasitic effect (p>0.05). Conclusions. The experimental extract (Allium sativum (garlic), Citrus limon (lemon) and Carica papaya (papaya) shows significant differences after being administered against intestinal parasitosis